Monitoring dan Evaluasi Kinerja Guru di Madrasah Ibtidaiyah Negeri 1 Palembang - Ibrahim, Ibrahim; Amelia, Nurhayati; Niswah, Choirun (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the monitoring and evaluation of teacher performance at MIN 1 Palembang. It employs a qualitative research method with a descriptive approach. The study involves 15 informants selected using purposive sampling, with data collected through interviews, observations, and documentation. Data analysis includes data collection, presentation, verification, and conclusion drawing, while data validity is ensured through triangulation. The results and discussion indicate that the monitoring and evaluation of teacher performance at MIN 1 Palembang have been effectively implemented through several stages: planning for monitoring and evaluation, conducting observations and assessments, analyzing evaluation results, follow-up actions and teacher coaching, as well as final reporting on the effectiveness of monitoring and evaluation of teacher performance at MIN 1 Palembang